2008
DOI: 10.1021/ef800681e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zeolite β from Kaolin and Its Catalytic Performance For FCC Naphtha Aromatization

Abstract: A hydrothermal synthesis method for β zeolite preparation using kaolin as the sole alumina source was investigated. This approach provided a choice to manufacture zeolite β with a low cost alumina source. The zeolite β samples were characterized by XRD, IR, SEM, XRF, DSC, and BET surface area measurements. Tunable crystallinity, higher meso-or macroporosity, higher thermal stability, and more Bro ¨nsted type acid sites of zeolite β can be obtained by properly controlling the synthesis conditions using this sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Kaolin clay is a cheap and plentiful raw material found in numerous geographical locations and has been used successfully in the synthesis of mesoporous aluminosilicates [12] and various microporous zeolite frameworks; ZSM-5, X/Y, β, and A [13][14][15][16][17][18][19][20][21][22]. A large part of these studies was the removal of impurities in the clays (typically quartz) via the thermal transformation of the untreated clay into metakaolin, which is itself catalytically active in the transesterification of waste cooking oil to alkyl esters [23].…”
Section: Introductionmentioning
confidence: 99%
“…Kaolin clay is a cheap and plentiful raw material found in numerous geographical locations and has been used successfully in the synthesis of mesoporous aluminosilicates [12] and various microporous zeolite frameworks; ZSM-5, X/Y, β, and A [13][14][15][16][17][18][19][20][21][22]. A large part of these studies was the removal of impurities in the clays (typically quartz) via the thermal transformation of the untreated clay into metakaolin, which is itself catalytically active in the transesterification of waste cooking oil to alkyl esters [23].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction (XRD) analysis Figure 1 depicts the X-ray diffraction (XRD) pattern of H-beta and ZnO-beta zeolite. The powder XRD pattern is the typical type for beta zeolite by comparing it with the reference beta zeolite (40). It was observed that, there is no visible difference between synthetic beta zeolite and zinc-modified beta zeolite.…”
Section: Resultsmentioning
confidence: 99%
“…1) showed typical diffraction peaks of beta zeolite (2θ = 7.8 • and 22.3 • ) when compared with a reference spectrum [42]. The peaks of ZnO-beta zeolite were lower in intensity than the peaks of H-beta zeolite.…”
Section: Xrd Analysismentioning
confidence: 90%